PENGARUH PENGUMUMAN RIGHT ISSUE TERHADAP TINGKAT KEUNTUNGAN DAN LIKUIDITAS SAHAM DI BURSA EFEK INDONESIA - ARDI NUGRAHA; ROCHMAWATI DAUD (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2013)
Announcement of right issue is information in order to investor to take decision in selling or buying stock. The objectives of this study are to give empirical evidence about the influences of right issue announcement to rate of return and stock liquidity in Indonesia Stock Exchange. The samples of this research consist of 12 companies that do the right issue announcement in Indonesia Stock Exchange during in 2006. Market model is used to estimate abnormal return and Trading Volume Activity (TVA). The data are analyzed using t-statistic. This study proofed that market will respond to the announcement right issue only at the day before announcement. The result of this research indicated that there are no different among rate of return and stock liquidity before and after the date of the right issue announcement.